Historical Trends in the Development of Ecotourism - pcadmin, Toshpo‘latova Mohinur (Academia One Publishing, 2025)
This article explores the historical evolution of ecotourism, tracing its origins and development from the mid-20th century to its establishment as a significant global phenomenon. Drawing on a comprehensive review of literature, it examines the socioenvironmental factors that spurred its emergence, key milestones in its growth, and its transformation into a sustainable tourism model. The study highlights how ecotourism arose as a response to the environmental degradation caused by mass tourism and evolved through innovative practices and policies aimed at balancing ecological preservation with economic benefits. The findings underscore ecotourism’s role in fostering environmental awareness and supporting sustainable development, particularly in regions with rich natural heritage.
Keywords: ecotourism; historical development